Mechanical properties of calcium phosphate reinforced polyhydroxyalkanoate (PHA) biocomposite - MI Najah, MI Najah; R Aisyah, R Aisyah; S Adzila, S Adzila; RHA Haq, RHA Haq (sage, 2023)
In the area of bone tissue engineering, the concept of using biomaterials based bone scaffolds in the regeneration of critical size bone defects is a key element to development of alternatives to allogenic and autogolous bone graft. Globally, countries all over the world is experiencing population aging besides other bone defects related case including trauma, pathology and congenital defects. Calcium phosphate (CaP) has received much interest for broad range of bone substitutes since its physicochemical properties can be conveniently tailored with close resemblance to human bone constituents. In this study the mechanical properties of Polyhydroxyalakanoate (PHA)/CaP composite were investigated. CaP was reinforced in PHA in the range from 5 wt% to 30 wt% and the tensile and impact properties of the composite were investigated. The addition of CaP showed fluctuation value in both tensile strength and impact strength starting with drop at approximately three times lower than neat PHA. The maximum tensile stress recorded at 15 wt% of CaP was 7.93 MPa along with elastic modulus of 102.416 MPa while the minimum tensile stress recorded at 30 wt% of CaP was 2.423 MPa with elastic modulus of 49.455 MPa. In parallel, the highest impact strength showed at 15 wt% of CaP was 5.761 kJ/m2 while the lowest mechanical strength recorded at 30 wt% of CaP content. Morphological analysis demonstrates the crack surface of each sample with CaP inclusion in supporting the development of brittleness in nature of biocomposite throughout the inclusion of CaP osteo-filler. Admittedly, the finding of this study will contribute to development of PHA based scaffolds for bone tissue with compromise mechanical properties along with their biological performance identical or similar to that of an ancient graft or transplant upon implantation.